Implementation Of Service Excellence In The First Experience Guest Become Guest Repeater At Hotel Chanti Semarang. - Tomi Dapot Tua Simarmata; Izza Ulumuddin Ahmad Asshofi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Guests who come to Hotel Chanti are expected to have first impression which is good, but the location, parking, location of the lobby makes a bad impression on guests. In addition, the projection to render first experience guest become repeater guest not running optimally. The research objective is to describe the implementation service excellence on first experience guest and describe how to seducefirst experience guest become a guest repeater. The research method used is a qualitative method with a descriptive type. Data collection techniques using observation techniques, interviews, and documentation. The research results consist of the first two things, implementation service excellence on first experience guest including serving with a positive and humble attitude, identifying guest needs, providing for guest needs, providing suggestions and appropriate solutions. Second, how to lure first experience guest become repeater guest including quality service, prioritizing guest wishes, providing the best experience, providing attractive promos, establishing good relations with guests, and providing rewards.